Sudut Pandang Etika dalam Pendidikan - Maharani, Cantika Putri; Alenanita, Adilia; Latifah, Arini Nur; Ernasari, Ernasari; Mahardika, I Ketut; Handoko, Sri (Peneliti.net, 2024)
It is recognized that efforts to break the dichotomy between values and science philosophically has received great attention from scientists, not only from the group itself, but also from religious group, especially after realizing the negative impact of scientific progress today with all its derivatives. However in this paper the writer studies from the perspective of learning methodology. This aspect is very crucial since science and religion could be integrated successfully when there is a valid and proper learning methodology. Through a study of science and value characteristic, integration between science and value is possible to be conducted. Therefore, methodology of learning which supports the integration of science and values can be done in some approaches and methods. They are strategy of learning, model of reflective learning, and model of collective decision making learning.